Multiparametric Magnetic Resonance Imaging in the Detection of Prostate Cancer - Durmus, T.; Baur, A.; Hamm, B. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Prostate cancer is the most common malignancy in men, but only about 10 % of patients die from that cancer. Recent studies suggest that not all patients benefit from a radical therapeutic approach. When prostate cancer is suspected, magnetic resonance imaging (MRI) can make an important contribution to cancer localization within the prostate. Many studies show that T2-weighted morphologic imaging should be supplemented by multiparametric MRI techniques including diffusion-weighted imaging, contrast-enhanced sequences, and MR spectroscopy. This approach detects aggressive prostate cancer with high sensitivity and specificity. The findings of multiparametric MRI additionally contribute information to the assessment of cancer aggressiveness. The use of these multiparametric MRI techniques will gain an increasing role in the clinical management of prostate cancer patients. They can help in establishing a definitive diagnosis with a minimum of invasiveness and may also contribute to optimal individualized treatment. This review article presents the different techniques of multiparametric MRI and discusses their contribution to the detection of prostate cancer. Moreover, this review outlines an objective approach to image interpretation and structured reporting of MRI findings using the PI-RADS criteria. The review concludes with an outline of approaches to prostate biopsy on the basis of MRI (transrectal ultrasound, direct MRI guidance of tissue sampling, and MRI-ultrasound fusion biopsy) and emerging future uses of MRI in the planning of focal treatment options and in the active surveillance of patients diagnosed with prostate cancer.Citation Format:• Durmus T, Baur A, Hamm B. Multiparametric Magnetic Resonance Imaging in the Detection of Prostate Cancer. Fortschr Röntgenstr 2014; 186: 238 – 246
Keywords: prostate; MR imaging; imaging sequences; neoplasms